(3QSGdI aj GdJYQja HGdTQaGA GdLhWjjfs - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s
(3ChdgG (B:s
(3bO JUaMJ eG SWQ GdLdI GdCYdGe ai TCf GdTQaGA GdLhWjjfhbO hbaJ Ydi eG CdehG Hg ef Gdfbhd hQHeG YKQJ ajeG eVi Ydi RjGOI hGdCeQ GdebUhO s
(3BNQgG (B:s
(3hbO PcQJ Pdc cdg ai cJGHi GdeSei HGdOQ GdSfi ai fSH ef HaGS ef Cgd GdfSH GdMSfi , adjfXQ gfGc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B20 - (3U(B24s
(3agQSJ GdQHGW (B: (3L(B2 (3U(B153s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B199 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B153 s
Keywords: (3GdJGQjNs